An Analysis Of The Credit Risk Determinant Using Internal Factor And Macroeconomy Data - Kornelia, Nisa; Mongid, Abdul; Suhartono, Suhartono (International Journal of Advanced Multidisciplinary, 2023)
This study analyzes the influence of internal bank factors and macroeconomic factors on non-performing loans (NPL) using data from the listed banks in Indonesia. We apply panel data analysis. The bank's internal and macroeconomic variables used in this study include inflation, GDP, BOPO, CAR, bank size, LDR, and ROA. The sample includes all listed banks that cover 40 banks for the period 2016 to 2021. The analysis technique uses descriptive analysis and linear regression analysis. The results of the study show that banks with a high capital adequacy ratio (CAR) own a low credit risk (NPL). While the inefficiency (BOPO) is positive and significant confirming the bad managed bank also having bad credit risk management. GDP growth has a positive coefficient but statistically not significant. Internal variables such as Bank Size, LDR and ROA are all not significant. The result confirmed that well capitalized bank take less risk and inefficient banks have bad credit risk management.